2021
DOI: 10.1007/s00193-021-00994-z
|View full text |Cite
|
Sign up to set email alerts
|

Blast enhancement from metalized explosives

Abstract: Experiments are carried out to determine the effects of particle size and mass loading on the free-field blast wave from spherical, constant volume metalized explosive charges. The charges are comprised of gelled nitromethane with uniformly embedded aluminum, magnesium, or glass particles. Particle sizes are varied over an order of magnitude with particle mass fractions up to 50%. Peak blast overpressures are directly measured within the fireball with piezoelectric pressure gauges and outside the fireball are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…This high-pressure zone then expands outward as a shock wave, with a sharp increase in pressure and temperature. The behavior of an explosive wave depends on a number of factors, including the energy and duration of the initial event, the density and composition of the surrounding medium, and the distance from the source of the explosion (Almustafa and Nehd 2023;Pontalier et al 2021).…”
Section: Discussion and Numerical Resultsmentioning
confidence: 99%
“…This high-pressure zone then expands outward as a shock wave, with a sharp increase in pressure and temperature. The behavior of an explosive wave depends on a number of factors, including the energy and duration of the initial event, the density and composition of the surrounding medium, and the distance from the source of the explosion (Almustafa and Nehd 2023;Pontalier et al 2021).…”
Section: Discussion and Numerical Resultsmentioning
confidence: 99%
“…According to Tanguay et al [4], the addition of aluminium or magnesium particles in a high explosive will lead to an increase in energy release of 5-6 times more than the bare high explosive. The results are observed in the far field [5] as an increase in the blast peak Communicated by D. Frost. overpressure. This is due to the fact that aluminium has a high density and a high heat of combustion.…”
Section: Introductionmentioning
confidence: 93%
“…The optically evaluated pressures from each of these studies demonstrated reasonable levels of agreement with gauge recordings between 0.8 and 5.2 m/kg 1/3 . Pontalier et al (2021) undertook a comprehensive optical analysis of shock wave propagation from metalized explosives across the intermediate scaled distance range (1.0-3.5 m/kg 1/3 ), measuring both fireball and fragment expansion rates. The results of which presented reasonably high variability of both arrival time and peak pressure when comparing nominally identical tests.…”
Section: Shock Wave Arrival Timementioning
confidence: 99%